Mapa de zonas sismogeneradoras en cuba (1998)
A new distribution of seismogenetic zones in Cuba is presented and discussed. Three main conditions are taken into account: tectonic-geological characteristics, geodynamic conditions and seismic activity of the Cuban block and surrounding areas. A new version of the classification system of Cuban seismogenetic zones is shown.